1971
DOI: 10.1002/1097-0142(1971)28:5<1245::aid-cncr2820280523>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Familial medullary thyroid carcinoma, pheochromocytoma, and parathyroid adenoma (Sipple's syndrome)Study of a kindred

Abstract: Fourteen patients from a kindred are presented, 10 of whom had Sipple's syndrome (pheochromocytoma and medullary thyroid carcinoma) and 6 of whom had coexistent parathyroid adenomas or hyperplasia. There was a high incidence of bilateral involvement in both pheochromocytoma and medullary thyroid carcinoma, 70% and 92%, respectively. Parathyroid adenomas or chief cell hyperplasia was associated with chemical or clinical evidence of hyperparathyroidism in two thirds of patients. There was no mortality associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1972
1972
1985
1985

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Until now it ' h a been commonly accepted that in its familial form MCT is inherited as an autosomal dominant trait with a relatively high degree of penetrance (3, 6,8,19,20,23,24,31,32). In the present study, at least one family (of probands nos 46 and 54) and possible one other (of proband no 12) fit in with such a pattern.…”
Section: Discussionsupporting
confidence: 58%
“…Until now it ' h a been commonly accepted that in its familial form MCT is inherited as an autosomal dominant trait with a relatively high degree of penetrance (3, 6,8,19,20,23,24,31,32). In the present study, at least one family (of probands nos 46 and 54) and possible one other (of proband no 12) fit in with such a pattern.…”
Section: Discussionsupporting
confidence: 58%
“…Other investigators have reported frequent simultaneous occurrence of these two endocrine tumors in adult bulls [22]. Sipple's syndrome of multiple endocrine neoplasms in man includes the coincidental occurrence of medullary thyroid carcinoma, pheochromocytoma, and parathyroid hyperplasia or adenoma [4,12,15,161, possibly from a basic defect in the development or regulation of neuroectodermal derivatives [7]. The bulls with pheochromocytomas and C-cell neoplasms in this study did not have parathyroid disease like that reported in Sipple's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The current view on the patho-physiological relation between these two lesions is that of a secondary hyperparathyroidism developing to counteract the hypocalcaemic effect of excessive calcitonin production by the thyroid neoplasm (Schimke et al Steiner ut al. 1968;Bartlett et al 1971;Catalona et al 1971). Since an inverse feedback relationship exists between the serum calcium level and parathyroid hormone production, this may result in normocalcaemia, which is the most frequent finding in patients with medullary thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%